Essays on banking and foreign exchange market instability - Skamnelos, Ilias (2003)
Financial intermediation has been associated with several risks. We study sunspot panics, information-based bank runs, contagion, uncertainty about consumption time preference, twin crises and a number of policies attempting to resolve these issues.